Colour, textural properties, cooking characteristics and fibre content of chicken patty added with oyster mushroom (Pleurotus sajor-caju) - Wan Rosli, W. I.; Solihah, M.A.; Aishah, M. S.; Nik Fakurudin,, N. A.; Mohsin, S. S. J. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The optical and textural properties of chicken patty formulated with different level of grey oyster mushroom (Pleurotus sajor-caju) at 0, 25 or 50% to replace chicken meat were investigated. The addition of up to 50% oyster mushroom to chicken patty formulations did not change colour a* (redness), compared with the control patty. Chicken patties containing oyster mushroom had lower L* value ranging from 51.02 – 52.65 compared to that of the control patty (57.86). All oyster mushroom-based patties had lower colour b* (yellowness) value compared to chicken patty without mushroom. The hardness of chicken patty decreased proportionally with the level of oyster mushroom. On the other hand, oyster mushroom-based patties were springier than the control patty. Chicken which was replaced with 25% of fresh mushroom, recorded the highest moisture retention (77.19%) and cooking yield (80.71%), respectively. However, replacement of 25% of oyster mushroom with chicken breast in chicken patty formulation was not change the moisture retention, fat retention and cooking yield compared to control patty. Chicken patty added with 50% ground oyster mushroom the highest concentration of total dietary fibre (TDF) at 4.90 g/100 g compared to chicken patty containing 25% of mushroom (3.40 g/100 g) and control (1.90 g/100 g). In summary, the addition of oyster mushroom in chicken patties has decreased the lightness, yellowness, hardness and chewiness while no changes were noted in the redness of the patties.